Toughening mechanism of barium titanosilicate glass-ceramics - Daming Sun; Tao Du; Qi Zhang; Lars R. Jensen; Deyong Wang; Junwei Ding; Jianan Zhao; Morten M. Smedskjaer (Materials & Design, 2024)
The fracture toughness of oxide glasses can be improved through controlled crystallization, forming glass-ceramics. However, to fully exploit their potential, an atomic-scale understanding of the toughening mechanism is needed. In this work, we investigate the structural origin of the variation in fracture toughness of barium titanosilicate glass-ceramics with varying crystallinity by combining experiments and molecular dynamics simulations. Generally, the glass-ceramics exhibit improved hardness, elastic modulus, and fracture toughness compared to the precursor glasses. The simulation results of 40BaO-20TiO2-40SiO2 glass-ceramics reveal that the differences can primarily be attributed to titanium bond switching events, namely, the change of the titanium coordination number under stress to dissipate mechanical energy. We also show that by tuning the content and aspect ratio of the formed fresnoite crystals, the fracture behavior of the glass-ceramics can be modified due to the redistribution of the stress field before fracture, which in turn controls the fracture path.